Oncostatin M Receptor-Targeted Antibodies Suppress STAT3 Signaling and Inhibit Ovarian Cancer Growth - Geethadevi, Anjali; Nair, Ajay; Parashar, Deepak; Ku, Zhiqiang; Xiong, Wei; Deng, Hui; Li, Yongsheng; George, Jasmine; McAllister, Donna M; Sun, Yunguang; Kadamberi, Ishaque P; Gupta, Prachi; et al. (Cancer research (Chicago, Ill.), 2021)
Although patients with advanced ovarian cancer may respond initially to treatment, disease relapse is common, and nearly 50% of patients do not survive beyond five years, indicating an urgent need for improved therapies. To identify new therapeutic targets, we performed single-cell and nuclear RNA-seq data set analyses on 17 human ovarian cancer specimens, revealing the oncostatin M receptor (OSMR) as highly expressed in ovarian cancer cells. Conversely, oncostatin M (OSM), the ligand of OSMR, was highly expressed by tumor-associated macrophages and promoted proliferation and metastasis in cancer cells. Ovarian cancer cell lines and additional patient samples also exhibited elevated levels of OSMR when compared with other cell types in the tumor microenvironment or to normal ovarian tissue samples. OSMR was found to be important for ovarian cancer cell proliferation and migration. Binding of OSM to OSMR caused OSMR-IL6ST dimerization, which is required to produce oncogenic signaling cues for prolonged STAT3 activation. Human monoclonal antibody clones B14 and B21 directed to the extracellular domain of OSMR abrogated OSM-induced OSMR-IL6ST heterodimerization, promoted the internalization and degradation of OSMR, and effectively blocked OSMR-mediated signaling . Importantly, these antibody clones inhibited the growth of ovarian cancer cells and by suppressing oncogenic signaling through OSMR and STAT3 activation. Collectively, this study provides a proof of principle that anti-OSMR antibody can mediate disruption of OSM-induced OSMR-IL6ST dimerization and oncogenic signaling, thus documenting the preclinical therapeutic efficacy of human OSMR antagonist antibodies for immunotherapy in ovarian cancer. SIGNIFICANCE: This study uncovers a role for OSMR in promoting ovarian cancer cell proliferation and metastasis by activating STAT3 signaling and demonstrates the preclinical efficacy of antibody-based OSMR targeting for ovarian cancer treatment.